2015
DOI: 10.12732/ijpam.v100i1.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Importance of Mitotic Asymmetry in Cyton-Based Models for Fse-Based Flow Cytometry Data

Abstract: We carry out computational inverse problem investigations to determine the importance of allowing for unequal label allocation to daughter cells during mitosis. Parameter estimations are performed using previously developed label-structured partial differential equation models that utilize cytons to account for variability in times between cell divisions as well as times until cell death. These models are augmented to allow for asymmetric cell divisions through inclusion of an additional model parameter. We em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(61 reference statements)
1
2
0
Order By: Relevance
“…However, for two thirds of the data sets, it was found that allowing asymmetric division does appear to lead to statistically significantly better agreement with the data. While there may be other confounding factors, the findings of [10] support the suggestion that there may be mathematical modeling error in the earlier CSFE labeled cell proliferation studies of [8,9,11,18]. Thus the findings in the present analysis are consistent with notion of a mathematical modeling misspecification in the earlier findings reported in [10].…”
Section: Cfse Data Setsupporting
confidence: 87%
See 1 more Smart Citation
“…However, for two thirds of the data sets, it was found that allowing asymmetric division does appear to lead to statistically significantly better agreement with the data. While there may be other confounding factors, the findings of [10] support the suggestion that there may be mathematical modeling error in the earlier CSFE labeled cell proliferation studies of [8,9,11,18]. Thus the findings in the present analysis are consistent with notion of a mathematical modeling misspecification in the earlier findings reported in [10].…”
Section: Cfse Data Setsupporting
confidence: 87%
“…The Bocharov, et al, investigations raised the question of whether cell proliferation models which allowed for asymmetric label division might be better suited to describe our human cell proliferation data. In [10] we revisited these data sets for the possibility of mathematical model misspecification. In these investigations we used statistically based model comparison tests and found seemingly contradictory results.…”
Section: Cfse Data Setmentioning
confidence: 99%
“…The availability of the code will facilitate the application of the method and simplify the development of extensions, e.g., towards multiple cell-types (Schittler et al, 2012), asymmetric cell division (Banks et al, 2015;Bocharov et al, 2013;Kapraun, 2014;Luzyanina et al, 2014) and alternative DALSP models (Banks et al, 2013a(Banks et al, , 2014(Banks et al, , 2015Kapraun, 2014;Luzyanina et al, 2014). In particular the implementation of a cyton-based model (Banks et al, 2013a(Banks et al, , 2014(Banks et al, , 2015Kapraun, 2014) would be interesting as these models allow for a fraction of nondividing cells. In addition to extensions, alternative parameterizations can be included, e.g., a parameterization of the probability density functions for a cell to divide and die at age a (as used in the cyton models) in contrast to a parameterization of the age-dependent rate of cell division and cell death.…”
Section: Discussionmentioning
confidence: 99%